2019
DOI: 10.3390/polym11020250
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Responsive Nanocomposite Hydrogels Based on PEG-b-PLGA Diblock Copolymer and Laponite

Abstract: Poly(ethylene glycol)-b-poly(d,l-lactide-co-glycolide) (PEG-b-PLGA) diblock copolymers are widely known as polymeric surfactants for biomedical applications, and exhibit high solubility in water compared to PLGA-b-PEG-b-PLGA triblock copolymers known as gelation agents. In order to overcome the difficulties in the preparation of thermo-responsive hydrogels based on PLGA-b-PEG-b-PLGA due to the low solubility in water, the fabrication of thermo-responsive hydrogels based on PEG-b-PLGA with high solubility in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
(46 reference statements)
3
21
0
Order By: Relevance
“…Our results corroborate with SANS studies of PLGA-PEG based block copolymers published previously [47,[54][55][56][57] keeping in mind the difference in composition, molecular weights and methods of preparation. For example, PEO-PLGA-PEO [55] and PLGA-PEG-PLGA [56] triblock copolymers were investigated using SANS.…”
Section: Nanoparticle Structuresupporting
confidence: 91%
See 2 more Smart Citations
“…Our results corroborate with SANS studies of PLGA-PEG based block copolymers published previously [47,[54][55][56][57] keeping in mind the difference in composition, molecular weights and methods of preparation. For example, PEO-PLGA-PEO [55] and PLGA-PEG-PLGA [56] triblock copolymers were investigated using SANS.…”
Section: Nanoparticle Structuresupporting
confidence: 91%
“…The combination of core-shell spherical model in combination with Debay form factor was used for the fitting the scattering profile from laponite free nanoparticles made of PEG-PLGA copolymers. The radius of a core and the micelles was found 1.6 and 4.7 nm, respectively, giving the shell thickness value to be of 3.1 nm [57]. We note here that the model used in our work is very close to the one reported in [57].…”
Section: Nanoparticle Structuresupporting
confidence: 78%
See 1 more Smart Citation
“…There have been other smart/stimuli‐responsive nanocomposite hydrogels based on various copolymer/clay combinations such as oligo(ethylene glycol)/laponite, [ 131 ] 2‐(2‐methoxyethoxy) ethyl methacrylate/fibrillar attapulgite, [ 132 ] laponite incorporated keratin/pluronic/chitosan blends, [ 152 ] poly (2‐methoxyethylacrylate‐ co ‐ N , N ‐dimethylacrylamide)/laponite, [ 118a,154 ] poly(ethylene glycol)‐ b ‐poly( d , l ‐lactide‐ co ‐glycolide)/laponite, [ 142 ] poly(2‐methoxyethyl acrylate)‐ co ‐( N , N ‐dimethylacrylamide)/laponite, [ 154 ] and poly (acrylamide‐ co ‐sodium acrylate)/laponite. [ 77 ] The responsive behavior of the copolymer/clay nanocomposite hydrogels is due to many factors such as phase transition temperature (LCST and UCST), inter/intra molecular hydrogen bond interaction, type of crosslinking, density and protonation–deprotonation of side/pendant groups of the polymer chains.…”
Section: Biomedical Applications Of Copolymer/clay Nanocompositesmentioning
confidence: 99%
“…They further revealed that transplantation of mouse myoblast C2C12 cells using thermoresponsive nanocomposite hydrogels dramatically enhanced tissue regeneration and functional recovery in model mice with skeletal muscle injury, whereas no recovery was observed for transplantation using PLGA-PEG-PLGA hydrogels. In 2019, Maeda et al reported on thermoresponsive nanocomposite hydrogel composed of laponite and PEG-PLGA diblock copolymers (Figure 7f) [69]. We synthesized PEG-PLGA with a high PEG-PLGA ratio of 1.27 and prepared the nanocomposite solution by mixing laponite aqueous suspension and PEG-PLGA aqueous solution.…”
Section: Thermoresponsive Nanocomposite Hydrogels Composed Of Laponitmentioning
confidence: 99%